Forming a System of Monitoring Business-Structures’ Activity in the Circular Economy Development - Konovalyuk, Iryna; Kucher, Anatolii; Danko, Tetyana; Vilhutska, Roksolana; Luchko, Halyna (European Journal of Sustainable Development, 2022)
The study’s goal is to develop a set of recommendations for forming the system of monitoring the business-structure activities in the circular economy development. To achieve this objective, the structural components of the system of monitoring the business-structures are identified; the adjustment vectors of the system of monitoring the business-structure activity are identified by taking into account the circular economy priorities; the solution is chosen to improve the system of monitoring the business-structure activity in the circular economy development; a model of information and analytical support for the process of forming the system of monitoring business-structure activity in the circular economy development is made up. The management mechanism to choose solutions from improving the system of monitoring the business-structures activities in the circular economy development is developed. Unlike existing ones, it is based on taking into account the relative importance of the factors that affect the formation of the system of monitoring, the links between them, and the factors' priority, which allows selecting from numerous alternative solutions those that have the greatest potential to improve the system of monitoring and establish the possible solutions' implementation sequence. In addition, a model of information and analytical support for the process of forming the system of monitoring the business-structure activity in the circular economy development is proposed. It differs from the existing ones in that it takes into account the mutual influence of the signs and conditions to improve the system of monitoring in relation to the development object, and makes it possible to increase the level of the information content of monitoring subjects when making corrective management decisions. Keywords: system, development, business-structure, circular economy, sustainable development, function, factor.